2020
DOI: 10.1038/s41598-020-70739-y
|View full text |Cite
|
Sign up to set email alerts
|

Zona pellucida shear modulus, a possible novel non-invasive method to assist in embryo selection during in-vitro fertilization treatment

Abstract: eliahu Levitas 3 & iris Har-Vardi 3* the present study investigated the association between oocyte zona pellucida shear modulus (ZpSM) and implantation rate (IR). Ninety-three oocytes collected from 38 in-vitro fertilization patients who underwent intracytoplasmic sperm injection were included in this case-control study. the Zp was modeled as an isotropic compressible hyperelastic material with parameter C 10 , which represents the ZpSM. computational methodology was used to calculate the mechanical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“… 47 Outside of these ranges, the average implantation rate was 6.70%. 46 , 47 After fertilization, optimal stiffness in the zygote is required for successful human embryonic development. 45 , 46 , 47 A study demonstrated that the viscoelastic properties of the zygote within hours after fertilization can predict blastocyst formation in humans and mice.…”
Section: Current Knowledge On Mechanobiology Of the Female Reproductive Systemmentioning
confidence: 98%
See 4 more Smart Citations
“… 47 Outside of these ranges, the average implantation rate was 6.70%. 46 , 47 After fertilization, optimal stiffness in the zygote is required for successful human embryonic development. 45 , 46 , 47 A study demonstrated that the viscoelastic properties of the zygote within hours after fertilization can predict blastocyst formation in humans and mice.…”
Section: Current Knowledge On Mechanobiology Of the Female Reproductive Systemmentioning
confidence: 98%
“…172 In that study, uterine con- outcomes. [45][46][47]152,153 However, before use of these biomarkers can become routine in clinical practice, there are many technical challenges that we must overcome. 152,153 First, we need to validate whether the biomechanical properties of bulk embryos are appropriate biomarkers.…”
Section: Uterine Contractionsmentioning
confidence: 99%
See 3 more Smart Citations